On the origin of Archaean TTGs by migmatization of mantle plume-related metabasalts : Insights from the Lake Inari terrain, Arctic Fennoscandia - Halla, Jaana; Joshi, Kumar Batuk; Luttinen, Arto; Heilimo, Esa; Kurhila, Matti (Elsevier B.V., 2024)
The conversion of basaltic crust into a thick, buoyant felsic crust of tonalite-trondhjemite-granodiorite (TTG) composition has been a fundamental process in the Earth's evolution during the Archaean Eon (4.03–2.50 Ga). The proposition that TTGs have formed as a result of the partial melting of hydrated mafic rocks is now well corroborated by geochemical modelling and experimental methods although these processes have only rarely been tested or documented by field studies. Here, we investigate the migmatite structures and major and trace element geochemistry of the 2.9–2.6 Ga Lake Inari TTG-metabasalt terrain in northern Finland, in the Lapland-Kola Province of Arctic Fennoscandia. The Lake Inari metabasalts geochemically resemble the flood basalts of the Phanerozoic oceanic plateaus. The TTGs show overall high Si and Na/K characteristics and have two coeval and intermingled geochemical endmembers, the low-HREE and high-HREE TTGs. Their variable geochemical signatures may reflect internal magmatic processes such as mingling of magmas that have experienced different evolutionary paths in terms of source mineralogy, degree of partial melting, differentiation and migration. The bimodal TTG-metabasalt association shows various migmatite structures such as metatexites, metatexite-diatexite transitions and massive diatexites that have formed in response to the weakening of the crust, melt segregation, extraction, migration and redistribution (SEMR) processes, and synanatectic strain. Rafts of the metabasalts probably represent the remnants of a basaltic upper ‘lid’ layer. We interpret the Lake Inari terrain to represent a widespread migmatization in deeper layers of an overthickened basaltic plateau persisting above a mantle plume, consistent with a stagnant or sluggish lid tectonic setting. Our results suggest that the formation of buoyant TTGs by partial melting of plateau basalts might have set off the evolution of continents. Peer reviewed